Chronic unpredictable stress exacerbates surgery-induced sickness behavior and neuroinflammatory responses via glucocorticoids secretion in adult rats. - Na Wang; Hong Ma; Zhe Li; Yalei Gao; Xuezhao Cao; Yanhua Jiang; Yongjian Zhou; Sidan Liu (PLoS ONE)
Methods Sprague-Dawley adult male rats (12-14 weeks old) were exposed to 14-day CUS and then subjected to partial hepatectomy 24 h after the last stress session. The rats were pretreated with an antagonist of the glucocorticoids (GCs) receptor RU486 (30 mg/kg, i.p.) 1 h prior to stress exposure. The behavioral changes were evaluated with open field test and elevated plus-maze test. The hippocampal cytokines interleukin (IL)-1β and IL-6 were measured on postoperative days 1, 3 and 7. Ionized calcium binding adaptor protein (Iba)-1, microglial M2 phenotype marker Arg1, brain derived neurotrophic factor (BDNF) and CD200 were also examined at each time point. Results CUS exacerbated surgery-induced sickness behavior. Exposure to CUS alone failed to alter the levels of pro-inflammatory cytokines in the brain. However, CUS exaggerated surgery-induced pro-inflammatory cytokines expression (e.g. IL-1β and IL-6) and upregulated the levels of Iba-1 on postoperative days 1 and 3. An additional significant decreased BDNF, CD200 and a lower level of Arg1 were also observed in the stressed rats following surgical procedure. Pretreatment with RU486 blunted the potentiating effects of CUS on surgery-induced sickness behavior and neuroinflammatory responses. Conclusion Chronic unpredictable stress enhanced surgery-induced sickness behavior and neuroinflammatory responses. Stress-induced GCs played a pivotal role in enhancing surgery-induced neuroinflammatory processes by modulation of microglia functions.